Actie "Campus op Pampus" voor het verkrijgen van meer woonruimte voor studenten. Serie van 6 foto's - Ruys, H.D., (1965)
Actie "Campus op Pampus" voor het verkrijgen van meer woonruimte voor studenten. Serie van 6 foto's.